Hubungan Antara Aktualisasi Diri Dengan Kecanduan Internet Pada Mahasiswa Universitas Muhammadiyah Surakarta - Putri, Salma Larasati Suryama; , Dr. Wiwien Dinar Pratisti, M.Si, Psi (2017)
The existence of the Internet as a new communications media provides a variety of convenience in presenting information in real-time. People use the internet with various motifs. One motive of someone using the internet is to actualize themselves. Self-actualization is shown by the activity of uploading photos, videos, and music features on the internet. This study aims: 1) to determine the relationship between self actualization with internet addiction. 2) to determine the level of internet addiction. 3) to determine the level of self actualization. 4) to determine effective contribution of self actualization on internet addiction at college student. Population in this research are all college students at Muhammadiyah University of Surakarta. The sample in this study are college students from Economic Bussines Faculty and Pharmacy Faculty amounted to 100 people. The sampling technique using cluster random sampling. The result of this study can be summarized as follows: 1) there is a significant negative correlation between self actualization with internet addiction at college student. 2) The internet addiction is on medium level. 3) The level of self actualization is high. 4) effective contribution of self actualization on internet addiction at 5,71%. This mean that there are 94,29% other factors that influence internet addiction such as internet facilitation availability, less supervision, and less of self control behavior.